Pengolahan Sampah Organik Dengan Metode Budidaya Maggot Di Kelurahan Larangan Indah - Hakim, Hakim; Tri Endangsih (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2023)
The increasing volume of waste generated by the community is a common problem that we often encounter in almost all big cities in Indonesia. Because it is necessary to process organic waste into goods that are useful and have economic value. Partners for Community Service Activities are the PKK group in Larangan Indah Village, Tangerang City. The purpose of this activity is to provide knowledge and understanding of the environmentally friendly movement through socialization activities and the practice of processing organic waste into compost and Maggot cultivation media for catfish food. The activity is carried out in 3 stages, namely (i) the first stage is theoretical debriefing and visual enrichment; (ii) the second phase of field practice to partners; and (iii) the third stage is in the form of guidance and assistance to partners. The target of this Community Service activity is to increase partners' knowledge and interest in processing organic waste, reduce the volume of organic waste in landfills, and provide business opportunities to partners. The results of the questionnaire assessment showed that training activities were able to increase partners' knowledge of the process of processing organic waste into compost and maggot cultivation, by an average of 85%. From the results of Community Service it can be concluded that processing organic waste using maggot is a very potential business opportunity, because in addition to reducing the volume of waste it can also provide added economic value.